Does corporate debt influence the firms’ growth after global financial crisis? evidence from Malaysian public listed companies - M. H., Nur Syabihah; Yahya, Mohamed Hisham; Chua, Mei Shan (Universiti Teknologi MARA, 2021)
This paper aims to investigate the impact of corporate debt on firm growth in Malaysia post Global Financial Crisis 2007-2008. Using a sample of 334 non-financial public listed companies in Bursa Malaysia from 2009 to 2018, this study finds that corporate debt is positively associated with firm growth. The possible reasons for this are; 1) the underdeveloped equity market in Malaysia that forced the firms to take up more debt as a financing resource and 2) the highly associated cost of issuing shares caused the firms to choose debt over equity, to finance the firms’ growth. The result is robust using the random effects panel regression model which mitigates unobserved heterogeneity. The finding supports the Pecking Order theory. The practical contribution of the study lies in the need for firms to deliberately design the application of debt in order to mitigate the associated cost of financial distress that arises from debt.